THE FLOUTING AND VIOLATING OF MAXIMS IN THE MAIN CHARACTERS’ UTTERANCES OF WILD CHILD MOVIE - -, ISTIQOMAH (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Cooperative Principle, Flouting Maxims, Violating Maxims, ResolvingStrategies, Intended Meanings, Wild Child Movie. Language becomes an important thing for people as the part of the society becausethey need language in their communication. In making communication more effectiveand to make sentences more acceptable to the hearer, it can be measured by applying cooperative principle consisting of four maxims proposed by Grice (2004), but in the real communication, that principle is not always being obeyed by the speaker and this phenomenon is called flouting and violating maxim. The writer conducts a study on “Wild Child” movie which shows the violating and flouting maxims phenomena occurring between the main characters. There are three problems of this study: (1) what maxims are violated and flouted in the main characters’ utterances of Wild Child movie in the exposition and conflict plot (2) How are the implied meaningsresolved by the interlocutors from the utterances being violated and flouted in WildChild movie (3) What are the intended meanings of the utterances being violated andflouted in Wild Child movie.This study uses the qualitative approach because the analysis is in the form of description rather than numbers. Then, the writer analyzes the main characters’ utterances. This study reveals that violating and flouting maxims are applied in themovie. There are 19 dialogues containing violating and flouting maxims, and the most violated and flouted is maxim of quantity. From violating and flouting maxims uttered by the main characters, their interlocutors use three resolving strategies: negotiation, contextual knowledge exploitation, and combination strategies in resolving the intended meanings. There are some intended meanings found, such as giving more information to hearer, maintaining good relationship, making jokes, supporting hearer, agreeing statement, persuading and showing surprise. Then, most of intended meanings from the utterances being violated and flouted are Showing Surprise and persuading hearer strategies. The most maxims that violated and flouted in the movie was quantity, it is shown by the main character in the movie by giving more information to the hearer in every conversation she made. The main character showed her ignorance and her being spoilt as a new student of Abbey Mount, a girlboarding school in rural of England. The writer suggests that the next researchers will analyze about the violating andflouting maxims in different plot, such as climax, falling action because the analysisabout resolving strategies will be more interesting. The writer also suggests that thenext researcher will use different theories about context that help to define theimplicit meaning, such as the relevance theory.